Healthcare worker´s use, opinion and knowledge of Personal Protective Equipment (PPE) during the Sars-CoV-2 pandemic: a cross-sectional study (Research, Society and Development, 2021)
The prevention and control of occupational infections require a broad approach with well-defined policies based on the characteristics of health institutions. In healthcare workers, occupational risk may be related to the handling of materials, chemical products, or equipment, which can be the cause of work accidents. Personal Protective Equipment (PPE) is one of the main safety measures to be adopted by professionals to ensure their protection. Thus, the present study aimed to evaluate the relationship between health workers and PPE and to assess the number of leaves of absence due to upper airway infection diagnosis and awareness of the risks they are exposed to at work. The vast majority of professionals reported using masks (55, 93.2%), closed shoes (50, 84.7%), and long-sleeved coat (44, 74.6%). However, there was less adherence to the use of procedure gloves (36, 61%), cap or hood (32, 54.2%), and eyewear (19, 32.2%). Although about one third of the workers reported using eyewear, almost half (47.5%) believe that this equipment should be mandatory during the workday. 93.2% of the interviewees mentioned using PPE because they are aware of the risks they are exposed to at work. Regarding the inferential analyses, there was no statistically relevant association between days away from work due to upper airway infections among health professionals participating in the study with age (p>0.05), gender (p>0.05), education (p>0.05), type of job (p>0.05), function (p>0.05) and UBS (p>0.05). Thus, it can be concluded that it is of great importance to increase the safety of health workers through training to demonstrate to professionals the importance of using PPE and the correct way to use this equipment.